Runoff control from dirt lots - Harner, Joseph P.; Murphy, James P. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A recent water quality survey assessment found nonpoint source pollution problems in a majority of Kansas surface waters - 85% of the monitoring sites were impaired by nutrients, 60% of the sites by bacteria, 55% by suspended solids and/or minerals, and 40% by oxygen-demanding substances. Swine producers have the responsibility to maintain the quality of ground or surface water near their production units. Outdoor dirt lots for confinement of swine are often overlooked as an area needing facilities for water pollution control.
Keywords: Swine; Runoff control; Dirt lots